Probe: The Message(s) are now the Media: A 2030 Outlook on McLuhan - Guarino, Frédéric (New Explorations)

(untitled) (New Explorations Association, 2023)
Marshall McLuhan’s seminal “the medium is the message” one-liner, title to Chapter 1 of his 1964 book Understanding Media is a formidable sum up of mid 20th Century media analysis. With a remarkable economy of semantics, McLuhan posited that the powers inherent to radio and television were so immense that the technology itself needed to be the focus. McLuhan’s insight is worth revisiting with an updated frame of reference towards 2030, given our current fragmented media landscape. Finite analog broadcast networks who wielded immense powers have now been replaced by an abundant digital emporium, itself ruled by oligopolistic technology platforms.